Effect of breed and corpus luteum on pregnancy rate of bovine embryo recipients - Nogueira, Ériklis; Cardoso, Gabriel Saravi; Marques Junior, Heitor Romero; Dias, Alexandre Menezes; Ítavo, Luís Carlos Vinhas; Borges, Juliana Corrêa [UNESP] (Sociedade Brasileira de Zootecnia, 2012)
The objective of this study was to evaluate pregnancy rates of recipients of different breed groups (Nellore and crossbreed), as well as the effects of size and type of the corpus luteum (CL) on plasmatic concentrations of progesterone and pregnancy rates of embryo recipients. A total of 152 heifers were synchronized with progesterone implants and on the day of embryo transfer, previously obtained by superovulation and frozen in ethylene glycol, the diameter and type of the corpus luteum (cavitary and compact) was measured and blood was collected for progesterone measurement. The pregnancy rate was 44.1%, with a diameter of corpus luteum higher in recipients that became pregnant (2.03±0.41) compared with non-pregnant ones (1.86±0.34 cm). Plasmatic concentrations of progesterone did not differ between pregnant (1.50±1.05) and non-pregnant (1.31±0.91 ng/mL) animals. The type of corpus luteum did not influence the pregnancy rates. Only Angus and crossbred Marchigiana differ among themselves in pregnancy rates (33.3 and 59.2%, respectively). The pregnancy probability was affected only by CL diameter, but not by P4 plasmatic concentration. Selection of the corpus luteum size at the time of embryo transfer is an important factor to increase pregnancy rates in recipients, and compact and cavitary corpora lutea do not influence the pregnancy rates of bovine embryo recipients. Nellore recipients have pregnancy rates that are satisfactory and comparable to crossbred (Bos taurus × Bos indicus) recipients.
Keywords: cavitary corpus luteum; Nellore; Progesterone; Ultrasound